If h(x) = x^3+ x and g(x) = 2x + 3, then g(h(2)) = ?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

We have the two functions h(x) = x^3+ x and g(x) = 2x + 3.

Now we need to find g(h(2)).

h(2) = 2^3 + 2

= 8 + 2

= 10

g(h(2))

= g(10)

= 2*10 + 3

= 20 + 3

= 23

Therefore g(h(2)) = 23.

Approved by eNotes Editorial
An illustration of the letter 'A' in a speech bubbles

Given that:

h(x) = x^3 + x

g(x) = 2x+ 3

We need to find g(h(2))

First we will determine the values of h(2).

==> h(2) = 2^3 + 2 = 8+2 = 10

Now we will substitute into g(h(2)

==> g(h(2)) = g(10)

Now we will substitute into g(x).

==> g(10) = 2*10 + 3 = 23

==> g(h(2)) = 23

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial